2022
DOI: 10.1186/s12974-022-02585-w
|View full text |Cite
|
Sign up to set email alerts
|

Chronic suppurative otitis media causes macrophage-associated sensorineural hearing loss

Abstract: Background Chronic suppurative otitis media (CSOM) is the most common cause of permanent hearing loss in children in the developing world. A large component of the permanent hearing loss is sensory in nature and our understanding of the mechanism of this has so far been limited to post-mortem human specimens or acute infection models that are not representative of human CSOM. In this report, we assess cochlear injury in a validated Pseudomonas aeruginosa (PA) CSOM mouse model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…We have previously shown that macrophages are the main immune cells present in the cochlea at the timepoint of OHC loss and found elevated levels of proinflammatory cytokines, which are known to be produced by activated macrophages. We also found that direct bacterial invasion is not the cause of hair cell injury in CSOM (12). These findings show a potential role of macrophages toward SHL in CSOM.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…We have previously shown that macrophages are the main immune cells present in the cochlea at the timepoint of OHC loss and found elevated levels of proinflammatory cytokines, which are known to be produced by activated macrophages. We also found that direct bacterial invasion is not the cause of hair cell injury in CSOM (12). These findings show a potential role of macrophages toward SHL in CSOM.…”
Section: Discussionmentioning
confidence: 58%
“…In CSOM, we have previously observed a significant increase of cochlear macrophages around the timepoint of hair cell death at 14 days after the infection, suggesting their recruitment to the cochlea (12). In the current study, we tested whether CX3CR1 is necessary for macrophage recruitment to the cochlea and whether the receptor depletion could potentially prevent OHC loss.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In inflammatory responses, activated macrophages release large amounts of cytokines, further increasing inflammatory responses 40 . NO, TNF-α and IL-6 are produced in acute and chronic inflammatory diseases 41 .…”
Section: Discussionmentioning
confidence: 99%